The Padma Multipurpose Bridge: Construction Challenges and Sustainable Management (MIST International Journal of Science and Technology, 2022)
An iconic building linking Bangladesh's southwest to its northern and eastern areas is the Padma bridge, which spans the third-largest river in the world with a complicated topology. By boosting production, employment, transportation, and the national and regional economy, this multipurpose bridge is projected to boost GDP growth by 1.2%. This study's primary goal is to pinpoint the greatest challenges encountered during Padma Bridge's construction and explain how sustainable management procedures might be put in place to address such difficulties. The most challenging tasks included finding a suitable site, dealing with complex river morphology, overcoming geotechnical barriers, controlling unfavorable environmental conditions, assembling massive construction equipment and materials, maintaining the construction schedule, and dealing with the COVID epidemic. To resolve these construction challenges, massive river training works and a unique pile foundation design that consists of six floating heaps and one center pile with the largest raking pile in the center were both utilized. To get around the difficulties in superstructural design, longer pre-assembled steel truss girders, pre-tensioned Super-T girders in viaducts, seismic isolation devices, and the largest friction pendulum bearings in the world were all made. Only a small number of people experienced COVID-19 without any fatalities or causing delays in the construction schedule since the Project was kept operational during the COVID-19 period by tightly enforcing the COVID laws and limits on people's mobility. The field of construction management would undergo a paradigm shift with this sustainable management of construction-related difficulties, which might later be used to design more intricate bridges.MIJST, Vol. 10, November 2022 (Special Issue: Padma Bridge): 09-21